Thermolytic Synthesis of Naphthalenes via Intramolecular Cyclocondensation of o-Phenylallylbenzaldehydes - Chang, Meng-Yang; Hsueh, Nai-Chen (Synthesis, 2018)
The development of intramolecular carbonyl-ene type cyclocondensation of oxygenated o-phenylallylbenzaldehydes in refluxing decalin is reported. The facile and easy-to-operate thermolytic rearrangement procedure generates substituted naphthalenes in good to excellent yields.
Keywords: carbonyl-ene type; cyclocondensation; o-carbonyl allylbenzenes; substituted naphthalenes